2020
DOI: 10.1002/ptr.6773
|View full text |Cite
|
Sign up to set email alerts
|

Jiawei Shengmai San herbal formula ameliorates diabetic associate cognitive decline by modulatingAKTandCREBin rats

Abstract: Memory loss is a complication of diabetes which requires new approaches to its treatment. Shengmai San (SMS) is a famous traditional Chinese formula containing Panax ginseng, Ophiopogon japonicas, and Schisandra chinensis, whereas Radix puerariae has many reported pharmacological uses. In this study the combination, as Jiawei SMS (J-SMS) was screened for its ability to reverse diabetes-associated cognitive decline in rats. This was assessed behaviorally in diabetic rats (Streptozotocin, 45 mg/kg), with biochem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Ahmed et al (2020) during an investigation on diabetic rats with cognitive failures showed that this formula can improve learning and memory during MVM and NORT tests, also can reduce blood glucose levels and raise AKT and CREB protein expressions that are responsible for learning and memory in the brain tissue. It has been suggested that puerarin is the most effective component of this herbal mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Ahmed et al (2020) during an investigation on diabetic rats with cognitive failures showed that this formula can improve learning and memory during MVM and NORT tests, also can reduce blood glucose levels and raise AKT and CREB protein expressions that are responsible for learning and memory in the brain tissue. It has been suggested that puerarin is the most effective component of this herbal mixture.…”
Section: Resultsmentioning
confidence: 99%
“…DCI is a neurodegenerative disease caused by diabetes and is characterized by dysfunction in cognitive functions such as verbal and visual memory, information processing speed, and executive function (Ahmed et al, 2020). Studies have revealed that diabetes increases the risk of cognitive impairment by a factor of 1.25–1.91 and that cognitive dysfunction in diabetes is present in all age groups, and hyperglycemia and hyperlipidemia are the key driving factors (Li et al, 2023; Nie et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Thus, this study was designed to formulate R-SMS that comprises four bioactive components, namely Puerarin, Ginsenosides, Schizandrin, and Ruscogenin. 41 All the components of R-SMS have been shown to be neuroprotective, especially antidepressant activity among chronic unpredictable mild stress mouse models. [47][48][49][50] During diabetes various major end organs, including the brain, have exhibited enhanced inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decoction for tonifying the kidney‐yin has shown to improve depression comorbidities in diabetes 39,40 . Recently, our group has shown that a combination of Shengmai San and Radix puerariae (R‐SMS) significantly improves learning and memory deficit in diabetic rats 41 . Therefore, this study was designed to explore the curative potential of R‐SMS to reverse diabetes‐associated depressive disorder in streptozotocin (STZ) rats and to elucidate its molecular mechanism at the nexus of PI3K/BDNF/SYN expression.…”
Section: Introductionmentioning
confidence: 99%